(untitled) (Contemporary Journal of Social Science Review, 2026)
This study was conducted to investigate the relationship between the prospective teachers’ growth mindset and their wellbeing. This was a quantitative study that has been conducted under the Positivist paradigm. The prospective teachers studying BS Education in a public and a private university have been sampled randomly. There were 140 male and female prospective teachers selected as a sample for the study. The data have regarding Prospective teachers’ growth mindset have been collected with the help of Growth Mindset Scale (GMS) and Psychological Wellbeing Scale by Ryff et al., (2018) was used for the data collection regarding wellbeing. The collected data were analyzed with the help of Descriptive statistics (Mean scores, Standard Deviation, Skewness and Kurtosis) and Inferential statistics (Pearsons’ r). Based on the results, it is concluded that a significantly positive and moderate correlation has been witnessed between Prospective Teachers’ Growth Mindset and Psychological.